Increased ABCC4 Expression Induced by ERRα Leads to Docetaxel Resistance via Efflux of Docetaxel in Prostate Cancer - Huang, Houbao; Li, Jing; Shen, Jing; Lin, Ling; Wu, Xu; Xiang, Shixin; Li, Yawei; Xu, Yujie; Zhao, Qijie; Zhao, Yueshui; Kaboli, Parham Jabbarzadeh; Li, Mingxing; et al. (Frontiers in Oncology, 2020)
Docetaxel is a major treatment for advanced prostate cancer, however, its resistance compromises clinical effectiveness. Estrogen receptor-related receptor alpha (ERRα) belongs to an orphan nuclear receptor super family and was recently found to be closely involved in cancer. In the present study, we found that ERRα was involved in docetaxel resistance in prostate cancer. Overexpression of ERRα conferred docetaxel resistance in prostate cancer cell lines and cells with ERRα downregulation was more sensitive to docetaxel. Among the drug resistance related genes, ABCC4 demonstrated synchronous expression after ERRα manipulation in cells. Moreover, both ERRα and ABCC4 were overexpressed in docetaxel resistant cell, which could be reversed by ERRα knockdown. Knockdown of ERRα also reversed the reduced drug accumulation in docetaxel resistant cell. We also demonstrated for the first time that ABCC4 was a direct target of ERRα as determined by CHIP and luciferase assay. Bioinformatics analysis revealed high expression of ERRα and ABCC4 in prostate cancer patients and a number of potential ERRα/ABCC4 targets were predicted. In conclusion, our study demonstrated a critical role for ERRα in docetaxel resistance by directly targeting ABCC4 and stressed the importance of ERRα as a potential therapeutic target for drug resistant prostate cancer.